Efficacy of Neoseiulus californicus and Phytoseiulus persimilis in suppression of Tetranychus urticae in young clementine plants - Abad-Moyano, Raquel; Pina, Tatiana; Pérez-Panadés, J.; Carbonell, Emilio A.; Urbaneja, Alberto (2017)
Tetranychus urticae is one of the most damaging tetranychid mites affecting clementine orchards in Spain, where natural control is insufficient. Furthermore, in clementine nurseries, tender foliage is highly susceptible to attack and natural enemies are almost always absent. Therefore, acaricides are often used indiscriminately. Alternative control measures are necessary, both in commercial orchards and clementine nurseries. In order to assess the efficacy of inoculative releases of N. californicus and P. persimilis to reduce T. urticae populations in young Spanish clementine plants, a semi-field experiment was conducted and repeated in three seasons (spring, summer and autumn). Phytoseiulus persimilis was highly effective in reducing both T. urticae infestations and the damage level inflicted on plants at both release rates evaluated (40 and 80 phytoseiids/plant) and all three periods considered. By contrast, N. californicus demonstrated low performance under certain conditions. The results of this study could be adapted and transferred to nurseries and young citrus plantations.